Implementation of Integrated Personnel and Payroll Information System (IPPIS) in Tertiary Institutions in Nigeria: Impact and Way Forward - Hussain A. Abubakar; Izunna Somadina Okwelogu; Victor Olugbenga Ayoko (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This paper titled “Implementation of Integrated Personnel and Payroll Information System (IPPIS) in Tertiary institutions in Nigeria: Impact and way forward” was carried out with the objectives of analyzing the impact of the implementation of Integrated Payroll and Personnel Information System (IPPIS) on tertiary institutions in Nigeria. Secondary data were used in the paper. The secondary data were collected from print and online publications. The paper's theoretical framework was anchored on Marx & Engel's Class theory (1971). A content analytical approach was employed in the research methodology. The study concluded that the implementation of the IPPIS policy on federal tertiary institutions in Nigeria has led to the disengagement of contract staff in federal tertiary institutions; slow down recruitment in federal tertiary institutions; led to violation of the autonomy of the institutions and the IPPIS policy did not suit the management structure and peculiarities of tertiary institutions in Nigeria. Based on these findings; the paper suggested that since the Integrated Payroll and Personnel Information System (IPPIS) is not designed to suit the administration and management of tertiary institutions in Nigeria, therefore, the federal government should remove all tertiary institutions from the Integrated Payroll and Personnel Information System (IPPIS).